2016
DOI: 10.1111/cwe.12157
|View full text |Cite
|
Sign up to set email alerts
|

How Off‐farm Employment Affects Technical Efficiency of China's Farms: The Case of Jiangsu

Abstract: Using three-wave survey data for four villages of Jiangsu Province in China, the present paper examines whether and to what extent off-farm employment affects the technical efficiency of agricultural production. The level of technical efficiency is measured using a stochastic frontier production function approach. Based on estimation results from instrumental variable panel quantile regressions we fi nd that there is a positive signifi cant effect of off-farm employment on the level of farm technical effi cien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 45 publications
4
22
0
1
Order By: Relevance
“…Zhang et al. () also found that there is a positive significant effect of off‐farm employment on the level of farm technical efficiency in China.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Zhang et al. () also found that there is a positive significant effect of off‐farm employment on the level of farm technical efficiency in China.…”
Section: Literature Reviewmentioning
confidence: 94%
“…It includes all work regardless of whether the individual has migrated to a location outside his/her village or works in the local region and lives in his/her village (Wang et al., ). As indicated previously, a number of studies have made empirical contributions to understanding the role of off‐farm work participation and various outcomes of interest such as household income, food security, and rural poverty (see e.g., Chang & Mishra, ; Mishra et al., ; Owusu et al., ; Zhang et al., ).…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…income, and may utilize these experiences in finding potential external buyers (Zhang et al, 2016). It is, thus, expected that non-agricultural working experiences (Non-Agri) may positively affect one's decision of to become a large-scale farmer.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, rural residents' per capita disposable income was $1476.42, which is just across the low-income level (i.e., below $1035). In the 21st century, as non-agricultural wages continue to rise, large-scale rural labor forces were transferred to the cities for non-agricultural employment and it led to agricultural recession [1,2], which urgently improved the productivity of agricultural labor and expanded the scale of agricultural management [3]. In reality, China's per capita arable land area is 0.08 hm 2 (1 hm 2 = 15 mu), which is less than half of the global average of 0.197 hm 2 .…”
Section: Introductionmentioning
confidence: 99%